A Modified Virtual Array ESPRIT Algorithm Based on Real Signal Subspace - Liu Ning; Shi Haoshan; Liu Liping; Yang Bo (Ieee, 2014)
A new ESPRIT method based on virtual array in the presence of coherent signals is presented. Using the received dates and its conjugate information, we reconstructed array data matrix. To reduce the complexity of algorithm, a real signal subspace can be obtained by a unitary transformation. Using the modified U-VC-ESPRIT which has small amount of calculation, we estimated DOA of non-circular coherent signal with arbitrary phase without array aperture reduction and effective element loss. The simulation results verified the effectiveness and superiority of the algorithm.
International Symposium on Antennas and Propagation (ISAP) -- DEC 02-04, 2014 -- Kaohsiung, TAIWAN
Keywords: DOA; Virtual Array; Unitary ESPRIT; coherent signals